Coral biomineralization: A focus on intra-skeletal organic matrix and calcification - FALINI, GIUSEPPE; FERMANI, SIMONA; GOFFREDO, STEFANO (Seminars in Cell & Developmental Biology, 2015)
In the recent years several papers and some reviews have dealt with characterization, localization and influence on the precipitation of calcium carbonate, of the organic matrix from scleractinian corals. In fact, it has been well established that coral calcification is a biological controlled process orchestrated in space and time by the organism also trough the secretion of organic matrix molecules because it has been well established that coral calcification is a biological controlled process, and thus is orchestrated in space and time by the organism also through the secretion of organic matrix molecules. In this review is presented a scientific path on the biomineralization of corals having as focusing point the intra-skeletal organic matrix, the molecules that are associated with mineral (aragonite). The review starts with a an overview on coral tissue, skeleton and tissue skeleton interface, describes the intra-skeletal organic matrix putting attention mainly on the proteins associated to aragonite and finally describes the in vivo and in vitro calcium carbonate precipitation experiments carried out aimed to evaluate the role of the organic matrix. The last paragraph reports studies on the role of the organic matrix in controlling calcification when corals are subject ocean acidification effects. The readers are expected to find a source of inspiration for new studies on the biomineralization of corals that are organic matrix addressed and merge diverse scientific disciplines.